Trichothiodystrophy‐associated MPLKIP maintains DBR1 levels for proper lariat debranching and ectodermal differentiation - Arjan F Theil; Alex Pines; Tuğba Kalayci; José M Heredia‐Genestar; Anja Raams; Marion H Rietveld; Sriram Sridharan; Sabine EJ Tanis; Klaas W Mulder; Nesimi Büyükbabani; Birsen Karaman; Zehra O Uyguner; et al. (EMBO Molecular Medicine)
Abstract The brittle hair syndrome Trichothiodystrophy (TTD) is characterized by variable clinical features, including photosensitivity, ichthyosis, growth retardation, microcephaly, intellectual disability, hypogonadism, and anaemia. TTD‐associated mutations typically cause unstable mutant proteins involved in various steps of gene expression, severely reducing steady‐state mutant protein levels. However, to date, no such link to instability of gene‐expression factors for TTD‐associated mutations in MPLKIP/TTDN1 has been established. Here, we present seven additional TTD individuals with MPLKIP mutations from five consanguineous families, with a newly identified MPLKIP variant in one family. By mass spectrometry‐based interaction proteomics, we demonstrate that MPLKIP interacts with core splicing factors and the lariat debranching protein DBR1. MPLKIP‐deficient primary fibroblasts have reduced steady‐state DBR1 protein levels. Using Human Skin Equivalents (HSEs), we observed impaired keratinocyte differentiation associated with compromised splicing and eventually, an imbalanced proteome affecting skin development and, interestingly, also the immune system. Our data show that MPLKIP, through its DBR1 stabilizing role, is implicated in mRNA splicing, which is of particular importance in highly differentiated tissue.